Dissection of the genetic architecture of rice resistance to the blast fungus Magnaporthe oryzae - Kang, Houxiang; Wang, Yue; Peng, Shasha; Zhang, Yanli; Xiao, Yinghui; Wang, Dan; Qu, Shaohong; Li, Zhiqiang; Yan, Shuangyong; Wang, Zhilong; Liu, Wende; Ning, Yuese; et al. (Wiley, 2016)
Resistance in rice cultivars to the rice blast fungus Magnaporthe oryzae is complex and is controlled by both major genes and quantitative trait loci (QTLs). We undertook a genome‐wide association study (GWAS) using the rice diversity panel 1 (RDP1) that was genotyped using a high‐density (700 000 single nucleotide polymorphisms) array and inoculated with five diverse M. oryzae isolates. We identified 97 loci associated with blast resistance (LABRs). Among them, 82 were new regions and 15 co‐localized with known blast resistance loci. The top 72 LABRs explained up to 98% of the phenotypic variation. The candidate genes in the LABRs encode nucleotide‐binding site leucine‐rich repeat (NBS‐LRR) resistance proteins, receptor‐like protein kinases, transcription factors and defence‐related proteins. Among them, LABR_64 was strongly associated with resistance to all five isolates. We analysed the function of candidate genes underlying LABR_64 using RNA interference (RNAi) technology and identified two new resistance alleles at the Pi5 locus. We demonstrate an efficient strategy for rapid allele discovery using the power of GWAS, coupled with RNAi technology, for the dissection of complex blast resistance in rice.